A pursuit differential game of many pursuers and one evader with coordinate-wise integral constraints on controls of players. - Alias, Idham Arif; Ibragimov, Gafurjan I.; Kuchkarov, Atamurat; Sotvoldiyev, Akmal (2013)
In this paper, a simple motion pursuit differential game of several pursuers and one evader is studied in R 2. Control functions of all players are subjected to coordinate-wise integral constraints. We say that pursuit can be completed if the state of a pursuer coincides with that of the evader at some time. We obtain sufficient conditions for completion of the differential game. The strategies of the pursuers are constructed based on the current values of control parameter of the evader. Also an illustrative example is provided.